Reinforcing Reading Comprehension with Summarizing Activities in Extensive Reading Class - Prasetyo, Halim Budi; Al Farhan, Miftah (Ahmad Dahlan Journal of English Studies, 2024)
Reading comprehension is crucial for it is indispensable to the formation of an individual's knowledge and perception about particular information obtained. In case of extensive reading context, reading comprehension can be facilitated through various strategies or activities, and one of them is summarizing activities. This study aims to scrutinize the summarizing activities performed by students to reinforce their reading comprehension of extensive reading projects in college. An interview study was employed as the research method by involving three English department students and one extensive reading lecturer as the research participants. Open-ended questions were used to guide the data collection process, and the data were further analyzed qualitatively. The results informed that students did the summarizing activities through several stages, such as dividing the book into several pages to be distributed to all group members, reading their respective pages, doing a focus group discussion (FGD) to discuss their readings, and making a comprehensive summary to be presented in front of the class. These activities were confirmed to facilitate the students in establishing better reading comprehension. In spite of that, any other activities to reinforce reading comprehension still need further investigation to provide several alternative options for use in more specific contexts.